2018
DOI: 10.3390/f10010012
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the Invasive Bark Beetle Phloeosinus aubei on Common Juniper Trees in the Czech Republic

Abstract: The small cypress bark beetle Phloeosinus aubei is considered an invasive pest in several central European countries, and we have determined its current distribution on common juniper trees (Juniperus communis) in the Czech Republic. The results indicated that P. aubei is widely distributed in the country but is more common in the east than in the west. The beetle was mainly detected on older, damaged trees and on stems with diameters > 3 cm. The apparently widespread and abundant populations of P. aubei co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 45 publications
(45 reference statements)
2
20
0
Order By: Relevance
“…Although this species was detected in only one sample with one extraction method (filtered ethanol) with low read numbers (11), it nevertheless remained in the OTU table after applying our cleaning steps; and although the possibility of a false positive (e.g. from contamination) cannot be definitively excluded, it may have been a result of traces of this species in the environment, especially in light of its invasive patterns observed recently (Fiala & Holuša, 2019). One possibility is regurgitated gut contents from a predator species in the trap (see Zizka et al., 2019).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although this species was detected in only one sample with one extraction method (filtered ethanol) with low read numbers (11), it nevertheless remained in the OTU table after applying our cleaning steps; and although the possibility of a false positive (e.g. from contamination) cannot be definitively excluded, it may have been a result of traces of this species in the environment, especially in light of its invasive patterns observed recently (Fiala & Holuša, 2019). One possibility is regurgitated gut contents from a predator species in the trap (see Zizka et al., 2019).…”
Section: Discussionmentioning
confidence: 91%
“…), whereas it is unknown if it additionally poses a threat to biodiversity. The species was unknown in Germany at the time of publication of the warning list, but has recently been spreading southward, through central, eastern and southern Europe (Fiala & Holuša, 2019). Although another congeneric species, Ips typographus (Linnaeus, 1758) (BOLD: ACT0826), a keystone pest species in the Bavarian Forest National Park (Müller, Bußler, Goßner, Rettelbach, & Duelli, 2008), was also detected in the same trap at 100% identity, these two species' barcode sequences cluster less closely together, and they do not share a BIN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiala and Holuša [3] investigated the distribution of the small cypress bark beetle (Phloeosinus aubei Perris) on common juniper trees (Juniperus communis L.) in the Czech Republic. They found that the beetle, which is considered an invasive pest in much of central Europe, mainly attacks older, damaged trees with stem diameters > 3 cm, and predicted that the beetle population density could increase on weakened and damaged trees even in protected areas and gardens.…”
Section: Contributions In Briefmentioning
confidence: 99%
“…From the beginning of the 20th century, the beetle began spreading from its origin in the Palearctic region to the south because spruce monocultures were being increasingly established in the south in Europe [8], unlike most other bark beetle invasions that extend from south to north [13,14]. I. duplicatus was first noted in eastern Czech Republic and south Poland in 1960s [15][16][17].…”
Section: Introductionmentioning
confidence: 99%